Results of an Experiment of Preparing Compost from Invasive Water hyacinth (Eichhornia crassipes) in Rupa Lake Area, Nepal - Kafle, Mohan Raj; Kafle, Gandhiv; Balla, Mohan Krishna; Dhakal, Lekhnath (Journal of Wetlands Ecology, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Water hyacinth Eichhornia crassipes (Jalakumbhi in Nepali) is an alien invasive species and now creating great environmental and economic problems covering major wetlands of the world. Nepal's wetlands are also greatly invaded by this obnoxious weed from which the social, economic and environmental sectors are facing serious problems for many years. In this context, Wetland Friends of Nepal (WFN) has carried out an experiment on making compost from this invasive weed in Begnas and Rupa Lake areas of Pokhara, Nepal with funding support from Toyota Environmental Activities Grant Program of Toyota Motor Corporation, Japan. This paper provides an overview of the findings of the experiment of preparing compost from Water hyacinth. Key words: Water hyacinth, compost, experiment, Nepal DOI: 10.3126/jowe.v2i1.1852 Journal of Wetlands Ecology, (2009) vol. 2, pp 17-19